Empirical patterns of firm growth and R&D investment: a quality ladder model interpretation - Zvi Griliches; Tor Jakob Klette (Institute for Fiscal Studies (IFS), 1999)
We present a model of endogenous Å²m growth with R&D investment and stochastic innovation as the engines of growth. The model for Å²m growth is a partial equilibrium model drawing on the quality ladder models in the macro growth literature, but also on the literature on patent races and the discrete choice models of product diÄrentiation. We examine to what extent the assumptions and the empirical content of our model are consistent with many of the the Å®dings that have emerged from empirical studies of growth, productivity, R&D and patenting at the Å²m level. The analysis shows that the model Ås well with a number of empirical patterns such as (i) a skewed size distribution of Å²ms with persistent diÄrences in Å²m sizes, (ii) Å²m growth independent of Å²m size, as stated in the so-called Gibrat's law, and (iii) R&D investment proportional to sales.
Keywords: 330